Value Chain Analysis of Rice Seed and Potato Tuber Seed in Vietnam: Case study in four provinces from North, Central and South - Ngo, Doan Dam; Baruah, Sampriti; Mohanty, Samarendu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The seed value chain analysis study on rice and potato was conducted during August to December 2019 to assess the composition, distinctiveness, strengths and weaknesses of Vietnam’s seed sector. The study examines relevant secondary sources of information and primary data obtained through field surveys using focus group discussion and key informant interviews in four provinces, namely: Bac Ninh and Thai Binh in the north; Quang Binh in the center and Can Tho in the south. The study results indicate that Vietnam has developed a robust seed sector with the involvement of diverse stakeholders throughout the seed value chain of rice and potato. The seed sector has contributed significantly to the success of Vietnam crop production over the past three decades. However, the existing seed sector has also shown many weak areas that need to be addressed for growth of crop production with increased efficiency, innovation, diversification and value addition. To support this goal, the study suggests several interventions and technological improvements in crop breeding, seed production and seed use especially for inbred rice, hybrid rice and potato. The study also proposes a detailed survey and analysis of Vietnam seed legislation to help make the seed sector more dynamic.